2018
DOI: 10.1007/s13730-018-0355-9
|View full text |Cite
|
Sign up to set email alerts
|

A case of IgG4-related kidney disease with predominantly unilateral renal atrophy

Abstract: A 73-year-old Japanese woman was diagnosed with type 1 autoimmune pancreatitis (AIP) without kidney lesions. She was treated with prednisolone (PSL) 30 mg/day, and her AIP symptoms promptly improved, after which the PSL dose was gradually tapered to 5 mg/day. Her renal function had remained normal (serum creatinine 0.7 mg/dL) until 1 year before the current admission without any imaging abnormalities in the kidney. However, during this past year her renal function gradually declined (serum creatinine 1.1 mg/dL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In some cases, with IgG4-RD without renal involvement, renal parenchymal lesions newly developed as a recurrence of the disease during the maintenance steroid therapy [71]. Since kidney is one of the most frequently affected organs of this diseases, annual imaging follow-up is necessary even if kidney is not involved at the first diagnosis.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, with IgG4-RD without renal involvement, renal parenchymal lesions newly developed as a recurrence of the disease during the maintenance steroid therapy [71]. Since kidney is one of the most frequently affected organs of this diseases, annual imaging follow-up is necessary even if kidney is not involved at the first diagnosis.…”
Section: Treatmentmentioning
confidence: 99%
“…To detect recurrence or newly developed lesions in the kidney, NAG, and b2 microglobulin (b2MG) have been thought to be promising biomarkers [72]. However, previous reports showed that such urinary biomarkers are not necessarily elevated in IgG4-TIN patients [71]. In addition, Mizushima et al documented that urine NAG and b2MG concentrations fluctuate despite successful corticosteroid therapy [67].…”
Section: Treatmentmentioning
confidence: 99%
“…[18,19] Renal pelvic lesions manifest as diffused wall thickening of the renal pelvis or soft-tissue mass encasing the pelvis, and the lesions exhibit similar intensity (on T2WI images) and enhancement pattern compared with parenchymal lesions. [13,14,17] Perinephric lesions are rare and appear as a rim-like lesion around the renal capsule, either diffuse or focal. [13,20] All 3 types of lesions of the kidneys can be unilateral or bilateral.…”
Section: Discussionmentioning
confidence: 99%